2021
DOI: 10.1021/acsnano.1c08557
|View full text |Cite
|
Sign up to set email alerts
|

Collective Phonon–Polaritonic Modes in Silicon Carbide Subarrays

Abstract: Localized surface phonon polaritons (LSPhPs) can be implemented to engineer light−matter interactions through nanoscale patterning for a range of midinfrared application spaces. However, the polar material systems studied to date have mainly focused on simple designs featuring a single element in the periodic unit cell. Increasing the complexity of the unit cell can serve to modify the resonant near-fields and intra-and inter-unit-cell coupling as well as to dictate spectral tuning in the far-field. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
4
1
Order By: Relevance
“…The observed dynamics can be understood via an effective medium picture: as the disk size is reduced, the effective permittivity of the overall hBN film is also reduced, resulting in the decrease of the resonance frequency; at some point, as the film thickness is fixed, a cutoff condition is met (see also discussion pertaining to Figure c). Numerical simulations also predict multiple resonance branches inside the RB, which are familiar phonon-polariton modes seen in a number of experiments. ,, The excitation of these modes is not clearly observed in our experiments. Taller hBN pillars are needed in order to observe phonon polariton modes, , as we show below for our 500 nm flake in Figure .…”
supporting
confidence: 59%
See 3 more Smart Citations
“…The observed dynamics can be understood via an effective medium picture: as the disk size is reduced, the effective permittivity of the overall hBN film is also reduced, resulting in the decrease of the resonance frequency; at some point, as the film thickness is fixed, a cutoff condition is met (see also discussion pertaining to Figure c). Numerical simulations also predict multiple resonance branches inside the RB, which are familiar phonon-polariton modes seen in a number of experiments. ,, The excitation of these modes is not clearly observed in our experiments. Taller hBN pillars are needed in order to observe phonon polariton modes, , as we show below for our 500 nm flake in Figure .…”
supporting
confidence: 59%
“…Midinfrared (mid-IR) radiation plays an important role in a wide range of applications covering thermal imaging, mimicry, , molecular and biosensing, , waste heat management, and radiative cooling, among others. Many diverse pathways have been proposed and examined recently to control mid-IR radiation, including such systems as plasmon-polaritons in graphene and doped semiconductors, all-dielectric metasurfaces, , and polar dielectrics. Of great interest are polar dielectrics, such as silicon carbide and hexagonal boron nitride (hBN), which, owing to their intrinsically strong phonon resonances, , offer unique avenues for light–matter interactions in the midwave and long-wave infrared bands (see also Supporting Information, section I). In addition, phonons can couple with optical modes forming hybridized phonon-polariton states. , …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The Reststrahlen band of polaritonic materials is located in the infrared part of the electromagnetic spectrum, where thermal emission is commonly spectrally located. It is theoretically shown that metamaterials made of nanoparticles of polaritonic materials can emit localized surface phonons (LSPhs) in their Reststrahlen band, causing narrow-band peaks in the near-field spectra. ,, It is proposed that the spectral location of the thermally emitted LSPhs can be modulated by varying the size and shape of the nanoparticles. ,, Tuning the spectrum of far-field thermal radiation by engineering the geometry of the polaritonic metamaterials has been demonstrated experimentally. , However, near-field thermal emission of LSPhs from polaritonic metamaterials has not been experimentally demonstrated yet. Indeed, while there have been several experimental studies on total (spectrally-integrated) near-field radiative heat transfer, ,,, measurements of the spectrum of near-field thermal radiation have been scarce. , A limited number of studies have experimentally explored the near-field response of polaritonic metamaterials to an external illumination using scattering-scanning near-field optical microscopy (sSNOM). ,, Using sSNOM, an external infrared electromagnetic field is shined to an AFM tip which is located at a subwavelength distance from the metamaterials.…”
Section: Introductionmentioning
confidence: 99%